The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1563/0.926.1
|View full text |Cite
|
Sign up to set email alerts
|

Immediate Loading of Single-Tooth Restorations: One-Year Prospective Results

Abstract: Immediate loading of splinted implant restorations is a growing trend, but limited clinical documentation hampers evidence-based treatment planning for single-tooth applications. This study prospectively evaluated the clinical efficacy of placing implant-supported, single-tooth restorations into immediate, full-occlusal loading. Sixty consecutive patients (intent-to-treat group) with 1 missing tooth between 2 intact teeth were treated with a total of 69 implants. At placement, final impressions were made and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
1
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 25 publications
1
23
1
1
Order By: Relevance
“…Mean implant bone loss rates were 0.43 ± 0.41 mm for PTTM implants ( n = 36) in the present PoP study and 0.98 ± 0.67 mm for the fully threaded implants ( n = 50) in the historical control study . Based on these data, a p value of <.001 was obtained by the Satterthwaite t ‐test.…”
Section: Discussionmentioning
confidence: 60%
See 4 more Smart Citations
“…Mean implant bone loss rates were 0.43 ± 0.41 mm for PTTM implants ( n = 36) in the present PoP study and 0.98 ± 0.67 mm for the fully threaded implants ( n = 50) in the historical control study . Based on these data, a p value of <.001 was obtained by the Satterthwaite t ‐test.…”
Section: Discussionmentioning
confidence: 60%
“…In the focus group, implant survival was 100% ( n = 22/22) and mean crestal bone loss from immediate provisionalization to the 1‐year follow‐up was 0.43 ± 0.41 mm (Table ). In comparison, the historical control study that used the same protocol with fully threaded implants reported 98.04% ( n = 50/51) implant survival and 1.05 mm (range = 0.38–2.69 mm) ( n = 50) of mean cumulative bone loss.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations